Implementation Planning Information Technology Service Management (ITSM) Iso 20000-Based in Guarantee Companies - Ahmad Kahfi; Nilo Legowo (Jurnal Indonesia Sosial Teknologi, 2024)
The helpdesk work unit was formed as a basic implementation of Information Technology Service Management (ITSM) implementation in the Company. In order to be able to measure the implementation of ITSM in the company, standardization of service management is needed, where currently, the standard used as a reference and is widely used is ISO 20000. ISO 20000 is a reference or best practice used in the implementation of business process management, which is expected to be able to respond to globalization developments where the ultimate goal to be achieved is to improve the quality and service in the Company. Currently, the constraints and problems faced by the Guarantee Company when ITSM has not been implemented include poor IT management, reduced levels of trust from stakeholders, weak control functions so that many risks occur and service level agreements (SLA) become unclear or do not have indicators in providing services.